Maternal synchronization of gestational length and lung maturation. - Valérie Besnard; Susan E Wert; Machiko Ikegami; Yan Xu; Caleb Heffner; Stephen A Murray; Leah Rae Donahue; Jeffrey A Whitsett (PLoS ONE, 2011)
Among all mammals, fetal growth and organ maturation must be precisely synchronized with gestational length to optimize survival at birth. Lack of pulmonary maturation is the major cause of infant mortality in preterm birth. Whether fetal or maternal genotypes influence the close relationship between the length of gestation and lung function at birth is unknown. Structural and biochemical indicators of pulmonary maturity were measured in two mouse strains whose gestational length differed by one day. Shorter gestation in C57BL/6J mice was associated with advanced morphological and biochemical pulmonary development and better perinatal survival when compared to A/J pups born prematurely. After ovarian transplantation, A/J pups were born early in C57BL/6J dams and survived after birth, consistent with maternal control gestational length. Expression of genes critical for perinatal lung function was assessed in A/J pups born after ovarian transfer. A subset of mRNAs important for perinatal respiratory adaptation was selectively induced in the A/J pups born after ovarian transfer. mRNAs precociously induced after ovarian transfer indicated an important role for the transcription factors C/EBPα and CREB in maternally induced lung maturation. We conclude that fetal lung maturation is determined by both fetal and maternal genotypes. Ovarian transfer experiments demonstrated that maternal genotype determines the timing of birth and can influence fetal lung growth and maturation to ensure perinatal survival.